Ion currents modulating oocyte maturation in animals. (2013) - Tosti, Elisabetta; Boni, Raffaele; Gallo, Alessandra; Silvestre, Francesco
Abstract : Growing oocytes are arrested at the first prophase of meiosis which is morphologically identified by the presence of a large and vesicular nucleus, called the germinal vesicle. The dissolution of the germinal vesicle marks the resumption of meiosis during which the oocyte undergoes massive modifications up to the second meiotic block, which is removed at fertilization. The interval between the first and the second meiotic block is defined as maturation and the events occurring during this period are crucial for ovulation, fertilization, and embryo development. Oocytes are excitable cells that react to stimuli by modifying their electrical properties as a consequence of ion currents flowing through ion channels on the plasma membrane. These electrical changes have been largely described at fertilization whereas little information is available during oocyte maturation. The aim of this review is to give an overview on the involvement of ion channels and ion currents during oocyte maturation in species from invertebrates to mammals. The results summarized here point to the possible functional role of ion channels underlying oocyte growth and maturation.